Neither by Land nor by Sea : The Rise of Electronic Remittances during COVID-19 - Dinarte-Diaz, Lelys; Jaume, David; Medina-Cortina, Eduardo; Winkler, Hernan (World Bank, Washington, DC, 2022)
Despite concerns that the COVID-19 economic collapse would torpedo international remittances, formal remittances to several developing countries ballooned early in the pandemic. This increase might, however, have reflected a shift from informal channels to formal ones rather than a change in actual flows. This paper employs Mexican data to explore this and finds that remittance channels did change. The rise in formal inflows was larger among municipalities that were previously more reliant on informal channels (for example, near a border crossing). Households there also experienced a disproportionate increase in bank accounts opened after lockdown measures. The paper also rules out hypotheses related to the US Coronavirus Aid, Relief, and. Economic Security Act and altruism.